Novel online calculator to predict reduced risk of early recurrence from adjuvant transarterial chemoembolisation for patients with hepatocellular carcinoma - Chao Li; Feng Shen; Wan Yee Lau; Timothy M Pawlik; Tian Yang; Wei-Yue Chen; Zhi-Peng Liu; Qing-Yu Kong; Li-Yang Sun; Yong-Yi Zeng; Ying-Jian Liang; Ya-Hao Zhou; et al. (eGastroenterology)
Background The role of adjuvant transarterial chemoembolisation (TACE) to reduce postoperative recurrence varies widely among patients undergoing hepatectomy with curative intent for hepatocellular carcinoma (HCC). Personalised predictive tool to select which patients may benefit from adjuvant TACE is lacking. This study aimed to develop and validate an online calculator for estimating the reduced risk of early recurrence from adjuvant TACE for patients with HCC.Methods From a multi-institutional database, 2590 eligible patients undergoing curative-intent hepatectomy for HCC were enrolled, and randomly assigned to the training and validation cohorts. Independent predictors of early recurrence within 1 year of surgery were identified in the training cohort, and subsequently used to construct a model and corresponding prediction calculator. The predictive performance of the model was validated using concordance indexes (C-indexes) and calibration curves, and compared with conventional HCC staging systems. The reduced risk of early recurrence when receiving adjuvant TACE was used to estimate the expected benefit from adjuvant TACE.Results The prediction model was developed by integrating eight factors that were independently associated with risk of early recurrence: alpha-fetoprotein level, maximum tumour size, tumour number, macrovascular and microvascular invasion, satellite nodules, resection margin and adjuvant TACE. The model demonstrated good calibration and discrimination in the training and validation cohorts (C-indexes: 0.799 and 0.778, respectively), and performed better among the whole cohort than four conventional HCC staging systems (C-indexes: 0.797 vs 0.562–0.673, all p<0.001). An online calculator was built to estimate the reduced risk of early recurrence from adjuvant TACE for patients with resected HCC.Conclusions The proposed calculator can be adopted to assist decision-making for clinicians and patients to determine which patients with resected HCC can significantly benefit from adjuvant TACE.